Sustainable Development and Indigenous Knowledge: The Role of Ancestral Communal Pools (Birket) in Southern Lebanon - Gharios, Georges (Blue Papers, 2026)
This article explores the pivotal role of ancestral communal pools, known as birket, in fostering sustainable water management, social resilience and climate adaptation in southern Lebanon. Rooted in centuries-old indigenous knowledge, these open-air reservoirs have historically enabled rural communities to manage scarce water resources through collective action and seasonal rituals. Despite the pressures of modernization, conflict and environmental degradation, many birket still exist – serving not only as functional infrastructure but also as vital symbols of cultural identity and solidarity. Based on a detailed survey and fieldwork in the historical region of Jabal Amel, this study highlights the practical and symbolic significance of birket, especially in border zones marked by displacement and ecological fragility. Examining their socio-ecological value and restoration potential, the article makes a case for integrating traditional water systems into national strategies for sustainable development and climate resilience – particularly in contexts where centralized infrastructure remains insufficient or ecologically unsound.